Sexualidade no âmbito escolar: ações lúdicas no processo de educação sexual - Lima, Lucineide Fagundes de (2019)
Early sexual initiation, unprotect sex practice, and lack of knowledge about the transmission of sexually transmitted infections (STIs) can be considered risky sexual behavior, making adolescents vulnerable. Here, we conducted discussions in the school environment promoting awareness that directly impacts the high rates of STIs and unintended pregnancy. The main doubts of the adolescents were identified, performed ludic activities through dynamics and virtual game, pertinent to health promotion. Our results indicate that students have a lack of knowledge about STIs and contraceptive methods, as well as lack of dialogue in school and family settings. Taken together, our data emphasize the school importance in the prevention of STIs, unintended pregnancy and health promotion.